PERAN DINAS PENDIDIKAN DAN KEBUDAYAAN DALAM PEMENUHAN FASILITAS SEKOLAH DASAR DI KABUPATEN KEPULAUAN MERANTI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The role of the education and culture service in the Meranti Archipelago Regency in the field of basic education is based on the laws and regulations relating to basic education and local regulations. Meranti District No 32 of 2016 meranti district, work programs and activities that will be carried out along with the targets and performance indicators of education services. For programs and activities in the field of basic education that have been carried out such as rehabilitation of schools, socialization of nine year compulsory education, and factors the obstacles that affect the implementation of the educational and cultural service duties of the Meranti Islands Regency in the field of basic education are human resources, targets and infrastructure, budget (finance), and community awareness factors. From the results of the research problem there are two main things that can be concluded. First, the role of the education and culture service in fulfilling elementary school facilities in the Meranti archipelago district. Second, inhibiting factors that influence the role of the education and culture service in fulfilling elementary school facilities in the Meranti archipelago district.This type of research is classified as sociological research, because in this study the authors directly conducted research at the location or place to provide a complete and clear picture of the problem under study. This research was conducted at the Office of Education and Culture, SD Negeri 3 Batang Malas, SD Negeri 3 Sialang Pasung, SD Negeri 6 Bungur, while the population and sample were all parties related to the problems examined in this study, the data sources used, Primary data, secondary data, and tertiary data, data collection techniques in this study were conducted by interview, and literature study.This study aims to determine how the role of the education and culture service in fulfilling primary school facilities in the Meranti archipelago district, to determine the inhibiting factors that influence the role of the education and culture service in fulfilling primary school facilities in the Meranti archipelago district.Keywords: The Role of the Department of Education and Culture, Kepulauan Meranti Regen